Modelling public behavioral intention to adopt Islamic banking in Uganda: the theory of reasoned action - Lujja, Sulaiman; Mohammed, MustafaOmar; Hassan, Rusni (Emerald Group Publishing Limited, 2016)
Purpose – Islamic banking (IB) has resulted in abundant cross-border financial flows and diversified economic inter-linkages with over US$2tn in assets that have extended beyond Muslim countries to more established global financial centres and other emerging economies. Despite this remarkable diffusion, numerous developing and least-developed countries are yet to embrace IB. This study aims to examine the factors that determine public intention to adopt IB in Uganda. Design / methodology /approach – This study undertook a quantitative approach where the theory of reasoned action (TRA) was used as a theoretical framework and structural equation modelling technique was applied to determine the relationship between attitude, subjective norm and public intention to adopt IB. Thus, a sample of 300 bank customers was surveyed using a questionnaire. Findings – Initially, the measurement model did not fit the data well. So, the model was modified by removing an indicator with a lower loading. Finally, the structural model under maximum likelihood estimate analysis confirmed a good model fit for the data. Key findings were as follows: attitude positively influenced intention to adopt IB, whereas subjective norm influence to intention is mediated by attitude. Furthermore, public intention to adopt IB in Uganda can be predicted by attitude (R2 0.89) which also mediates the prediction of subjective norm to intention (R2 0.58). Originality/value – To the best of the authors’ knowledge, no study has used the TRA on the feasibility and adoption of IB. Thus, the present study is relevant in extending the theoretical body of knowledge by validating the TRA in a new field.